Stress Ulcer Prophylaxis – Daily Practice in a Medical Ward for Two Years - Coelho, Ângela; de Andrade Maia, Lara; Oliveira Ferreira, Marta; Oliveira, Liliana; Salomão, Jorge; Cardoso, Nuno; Neves, Pedro; Duarte, Augusto (Portuguese Journal Internal Medicine, 2015)
Introduction: The prevention of stress ulcers (SU) is well established in intensive care units, however, recently, this practice has been extended to medical wards, despite little evidence to support it. Its implementation is based on the association of various risk factors, however, studies show that 56 to 71% of patients under SU prophylaxis in medical wards have no such criteria. Objective: With this reality in mind, a trial was developed with the intent to create, apply and audit the implementation of a SU prophylaxis protocol in an Internal Medicine ward, over two years. Material and Methods: To this end, after reviewing the criteria for SU prophylaxis in medical patients in 2011, an audit was performed without previous notice followed by training of the clinical staff. In 2012 and 2013 new audits were carried out. Results: From 2011 to 2012, a statistically significant improvement in the guidance of patients was identified (57.8% to 70%), however, there was a statistically significant setback from 2012 to 2013 (52.5%). Discussion: The contributing factors for the improvement seen from the first to the second audit may have been the elaboration of the SU prophylaxis protocol along with staff training. Such improvement was dissipated in the third audit, probably because of the controversy that surrounds this subject and the absence of new training activities. Conclusion: This trial intends to remind that not all hospitalized patients have criteria for SU prophylaxis and that is important to define protocols adapted to the reality of each institution as well as maintaining permanent staff training.